Histological analysis of a clinical case of central giant cell lesion treated with triamcinolone - Neri, Júlia dos Santos Vianna; Fortuna, Tila; Couto, Milena; Marchionni, Antônio Márcio Teixeira; Reis, Sílvia Regina de Almeida; Medrado, Alena Ribeiro Alves Peixoto (Journal of Oral Diagnosis, 2017)
Introduction: Central giant cell lesion (CGCL) is an osteolytic lesion mainly found in gnathic bones of children and young adults. It is a benign lesion with variable clinical and radiographic behavior but it may be aggressive. Intralesional corticoid application has been proposed as an alternative and complementary procedure to radical surgical treatment, to minimize functional and aesthetic damage. Objectives: This paper aims to report a case of a pediatric patient with CGCL of the jaw, which was treated withconservative treat- ment of two intralesional applications of triamcinolone and discuss if there is an ideal waiting period between nonoperative treatment and the need for surgical intervention. Methods: This report shows a quantitative analysis of histological alterations induced by intralesional infiltrations of triamcinolone into a clinical resistant CGCL. A 7-year-old patient was submitted to a conservative treatment of two intralesional applications of triamcinolone into a mandible CGCL. Results and Conclusion: Histological evaluation showed reduction in the number of blood vessels and of giant multinucleated cells, besi- de an increased collagen production. The triamcinolone induced histological alterations seem to interfere in the clinical behavior of the lesion thus, recommending a less radical surgical treatment.